2021
DOI: 10.1111/jfpp.15234
|View full text |Cite
|
Sign up to set email alerts
|

Rheological properties of thickened barium liquids prepared with xanthan gum‐based thickener and barium powder used in the diagnosis of dysphagia: Effect of thickener concentration and serving temperature

Abstract: In this study, thickened barium liquids (TBL) were prepared by mixing a xanthan gum (XG)‐based thickener at different concentrations (1.0%–3.0%) with a barium powder. The rheological properties of TBL and thickened non‐barium liquids (TNL) at different thickener concentrations were examined under steady and dynamic shear conditions. The values of flow and dynamic rheological parameters (K, σoc, G′, and G″) of TBL were considerably higher than those of TNL. The extents of the TBL thixotropy loops decreased with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…Moreover, the extent of viscosity increase was varied depending on the thickening products, particularly the type of prevailing hydrocolloid used in the product formulation. This result is consistent with previous literatures which showed that the mixture of 25% (w/w) barium sulfate suspension and thickening powders could give rise to further thickening effect, thus resulting in higher viscosity or consistency of the liquid (Barbon & Steele, 2019; Park & Yoo, 2021; Park et al, 2019; Popa Nita et al, 2013; Steele et al, 2013). However, none of these works have deduced explicitly that the increase in viscosity could simply be predicted by a simple shift factor, particularly in the gum‐based thickening powder as indicated in this study (see also Figure 2b).…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…Moreover, the extent of viscosity increase was varied depending on the thickening products, particularly the type of prevailing hydrocolloid used in the product formulation. This result is consistent with previous literatures which showed that the mixture of 25% (w/w) barium sulfate suspension and thickening powders could give rise to further thickening effect, thus resulting in higher viscosity or consistency of the liquid (Barbon & Steele, 2019; Park & Yoo, 2021; Park et al, 2019; Popa Nita et al, 2013; Steele et al, 2013). However, none of these works have deduced explicitly that the increase in viscosity could simply be predicted by a simple shift factor, particularly in the gum‐based thickening powder as indicated in this study (see also Figure 2b).…”
Section: Resultssupporting
confidence: 93%
“…Unlike the gum-based samples, the η 50 of barium thickened liquids from modified starch-based powder, that is, TU sample, was not invariant to those of the nonbarium thickened liquids. As a result, the shift factor cannot be defined for this case and its shifting result was omitted from resulting in higher viscosity or consistency of the liquid (Barbon & Steele, 2019;Park & Yoo, 2021;Park et al, 2019;Popa Nita et al, 2013;Steele et al, 2013). However, none of these works have deduced explicitly that the increase in viscosity could simply be predicted by a simple shift factor, particularly in the gum-based thickening powder as indicated in this study (see also Figure 2b).…”
Section: Extensional Rheologymentioning
confidence: 79%
See 2 more Smart Citations
“…Oropharyngeal dysphagia refers to swallowing problems when transporting solid or liquid food from the mouth to the esophagus that can lead to aspiration pneumonia [ 1 , 2 ]. Therefore, liquid foodstuffs are commonly thickened with commercial thickener powder to modify their viscosity [ 3 , 4 ]. The effective treatment of dysphagia requires pertinent viscosity-modification of thickened liquids because inaccuracies in preparing them at the targeted viscosity can cause aspiration [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%